스트레스해소법에 따른 한부모가정 부모의 스트레스와 생활만족도와의 관계 연구 - 중부권 소도시를 중심으로 - 오승하; 조성제; Oh, Seung-ha; Cho, Sung-Je (한국정보전자통신기술학회 논문지, 7(1), 2014)
This research aims to identify relationships between stress level of parents in single parent families and life satisfaction in accordance with methods of getting rid of stress. Subject of the research were 260 parents in single parent families, centering on small towns in midsection sphere based on answers to questionnaire executed from March 1, 2013 to July 31, 2013. Collected data were analyzed by executing frequency analysis, factor analysis, t-test, one-way ANOVA, correlation analysis, regression analysis, etc. and an empirical verification was performed at 5% of significance level. From the result of the research, stress level appeared according to factors in a sequence of economic power, physical strength, social relation, family, mentality, etc. and significant influence to life satisfaction was found depending on factors such as stress removing methods and controlling effect. And minor factors were shown in a sequence of finance, emotion and acknowledgement. Suggestive points of the research are thought to be significance of stress removing method to the enhancement of life satisfaction, which will be a good material for the establishment of fundamental supporting plans and development of programs for single parent families. 본 연구는 스트레스해소법에 따른 한부모가정 부모의 스트레스와 생활만족도와의 관계를 파악하고자 한다. 연구대상은 2013년 3월1일부터 7월31일까지 중부권 소도시를 중심으로 한부모가정 부모 260명을 대상으로 설문조사를 실시하였다. 자료분석은 빈도분석, 요인분석, t-test, 일원변량분석, 상관분석, 회귀분석을 실시하였으며, 실증분석은 유의수준 5%에서 검증하였다. 연구결과 스트레스는 경제, 신체, 사회 및 일상, 가족, 심리요인 순으로 높게 나타났고, 스트레스요인의 해소법과 조절효과에 따른 해소정도가 생활만족도에 유의미한 영향을 나타냈다. 그리고 하위요인은 재정, 정서, 인지적 순으로 유의미하게 나타났다. 연구의 시사점은 생활만족도 증진에 스트레스해소법이 유의미함으로, 한부모가정 부모에 대한 기초적인 지원정책수립과 프로그램개발의 자료가 될 것으로 사료된다.